Relational research ethics and disengagement from collaborative research projects in higher education: A conceptual analysis - Madikizela-Madiya, N. (South African Journal of Higher Education, 2022)
Research collaboration is a common practice in higher education, and so is the discourse of research ethics. However, the colonial orientation of some research as well as the managerial models of higher education practices undermine the connectedness and relationality of collaborative research. In this article, I argue this point with a focus on disengagement or withdrawal of collaborators from research projects before they are completed. I argue that this practice has ethical implications at various levels, especially the level of the researched or colonised communities. Drawing from multi-disciplinary literature, I follow a conceptual analysis method, focusing on research collaboration, research ethics and disengagement. The article identifies the types and benefits of collaborative research, as well as common reasons and ethical implications of disengagement from such projects. It concludes by recommending an extension of research ethics regulations to incorporate disengagement, in consideration of the relationality of collaborative research projects.